AntagomiRs: A novel therapeutic strategy for challenging COVID-19 cytokine storm. (April 2021) - Gangemi, Sebastiano; Tonacci, Alessandro
Abstract: Is it possible to develop a reliable, safe treatment for the widespread COVID-19 pandemic shortly? COVID-19 is characterized by a disruptive cytokine storm, quickly and often irreversibly damaging the patient's lungs, as its main target organ, leading to lung failure and death. Actual experimental therapies are trying to reduce the activation of some specific cytokines, such as IL-6, somewhat reducing the burden for the patient. However, they are often unable to block the whole storm occurring at the cytokine level. In presence of the cytokine storm, especially in severe patients, antagomiRs, already demonstrated to be efficient and secure in cardiovascular disease, could represent a useful alternative to such treatment, customizable upon the disease specificities and applicable to other coronaviruses possibly associated with such clinical manifestations, while a reliable, efficient vaccine is being distributed.